Supervision Management in Improving Madrasah Achievement in State Aliyah Madrasas - Sutarno Sutarno (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This study aims to reveal Supervisory Management in an effort to increase outstanding Madrasahs in Muaro Jambi district, this is in line with our educational goals, namely to educate thnation's life, that supervisors are one of the important subjects in the educational process for students and institutions to achieve. This research tries to dig deeper into how Supervisory Management achieves outstanding Madrasahs, especially at the Sungai Gelam State Aliyah Madrasah. Jambi Muaro district. This research used a qualitative approach by employing observation, interviews, and documentation as data collection methods. Data analysis techniques include data reduction, data presentation, and verification or drawing conclusions. Checking the validity of the data by extending participation, the accuracy of observations, triangulation, and consulting the supervisor. Does this study aim to find out (1) how is the management of supervisors at the Sungai Gelam Muaro Jambi State Aliyah Madrasah? (2) What are the efforts to increase the achievement of Sungai Gelam Muaro Jambi State Aliyah Madrasah? (3) How is the evaluation of the implementation of the supervisor's task program in improving the achievement of Sungai Gelam Muaro Jambi State Aliyah Aliyah?